2007
DOI: 10.1002/bies.20561
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral nuclear import: a complex interplay between virus and host

Abstract: Although the capacity to infect non-dividing cells is a hallmark of lentiviruses, nuclear import is still barely understood. More than 100 research papers have been dedicated to this topic during the last 15 years, yet, more questions have been raised than answers. The signal-facilitating translocation of the viral preintegration complex (PIC) through the nuclear pore complex (NPC) remains unknown. It is clear, however, that nuclear import is the result of a complex interplay between viral and cellular compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 109 publications
0
45
0
Order By: Relevance
“…Previous studies in this field were directed at HIV-1-encoded molecules (e.g., matrix, Vpr, integrase, and cPPT) that harbor nuclear import activity (9,39). However, our laboratory demonstrated that none of the previously reported karyophilic elements encoded by HIV-1 is essential for the cell cycle independence of HIV infection (44).…”
Section: The Ability Of Human Immunodeficiency Virus (Hiv) To Infect mentioning
confidence: 87%
“…Previous studies in this field were directed at HIV-1-encoded molecules (e.g., matrix, Vpr, integrase, and cPPT) that harbor nuclear import activity (9,39). However, our laboratory demonstrated that none of the previously reported karyophilic elements encoded by HIV-1 is essential for the cell cycle independence of HIV infection (44).…”
Section: The Ability Of Human Immunodeficiency Virus (Hiv) To Infect mentioning
confidence: 87%
“…Here, we studied the molecular interaction between TRN-SR2 and HIV-1 IN to define the NLS in IN. Because IN has been proposed before to play a role in HIV nuclear import (5,6,11,12,50) (31). Multiple IN mutations were inserted into viruses and tested for their impact on viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…After virus entry and reverse transcription, the preintegration complex (PIC) 5 translocates to the nucleus, and the viral DNA is integrated into the host chromatin. HIV crosses the nuclear membrane through active nuclear import of the PIC (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations